Berebut Ruang Publik Sekolah Pasca Orde Baru: Studi Kasus Pertarungan Politik Ideologi di Kerohanian Islam (ROHIS) - Fachri Aidulsyah (Universitas Gadjah Mada, 2016)
The Burgeoning of the Islamic Movements in Indonesia –especially originated from the Middle East- that growing up since authoritarian era have been influencing various institutions in Indonesia, including educational institution in Ex Karesidenan Surakarta region. In this research, I exhibit that Ex-Karesidenan Surakarta region has become a centre of Islamic movement turbulence in Indonesia. Since pre-Independence era, various Islamic ideologies actualize and compete with each other –from traditionalist, modernist, and radical movement- for gaining influence in these regions. This research discusses the implication of contestation among Islamic ideologies in Senior High School that affect the scramble of educational public sphere and interchange cultural symbols in these institutions. This paper attempts to address two main issues; 1) to examine various contestation and hegemony models performed by each of Islamic ideologies for gaining influence in the public educational sphere –epecially Kerohanian Islam (ROHIS); 2) to explore various political ideologies in each Islamic movement that led to different meanings towards Islam, state, and democracy.